Butyric acid glycerides as substitutes for antibiotics as growth enhancers in the diet of nursery piglets - Marchiori M.S.* (2024)
© 2023This study aimed to determine whether the addition of butyric acid glycerides as substitutes to conventional growth promoters can provide adequate zootechnical performance and intestinal health in healthy piglets in the nursery phase. We used 90 male piglets (average weight of 6.5 kg) subdivided into five treatments with six replicates per treatment. The treatments had the same basal diet: NC—negative control (without growth promoter), PC—positive control (with gentamicin, oral), PSB—protected sodium butyrate, FSB—free sodium butyrate, and TRI—tributyrin. In these animals, zootechnical performance was evaluated on days 1, 10, 20 and 39, microbiological analysis on days 14 and 39, hematocrit, blood biochemistry and intestinal histology, intestinal oxidation and antioxidation on day 39. The average daily weight gain was higher in the TRI group on days 21 to 39 in the nursery (P = 0.03), with more significant weight gain from 1 to 39 days (P = 0.05). There were higher leukocyte counts in the PC group than in the TRI group and higher lymphocyte counts in the PC treatment than in the NC or TRI groups. Escherichia coli counts were lower in the PC, followed by the PSB and TRI groups on day 39 (P = 0.01). Lower crypt depths were found in the TRI and FSB groups, followed by PC, than in the NC group (P = 0.01). Higher values for crypt villosity ratio were found in the FSB and TRI groups than in the NC group (P = 0.05). Lower lipid peroxidation was found in analyzes of serum oxidative status (LPO: P = 0.01), associated with greater activities of superoxide dismutase – SOD (P = 0.08), glutathione S-transferase – GST (P = 0.09) in PSB and TRI groups than in the NC group. In conclusion, the use of butyric acid in the form of tributyrin can be used as growth enhancers in piglets in the nursery phase.